High-Fat Diet Alters Circadian Rhythms in Mammary Glands of Pubertal Mice - Sundaram, Sneha; Johnson, LuAnn K.; Yan, Lin (Frontiers in Endocrinology, 2020)
Childhood obesity in girls is associated with early puberty and menarche. Breast tissue exhibits circadian rhythms; environmental cues may alter the rhythms. We hypothesized that a high-fat diet (HFD) disrupts circadian rhythms in pubertal mammary glands. Weanling female C57BL/6 mice were fed the standard AIN93G diet or an HFD (providing 16% or 45% of energy from soybean oil) for three weeks. Mammary glands were harvested from six-week-old mice every four hours on Zeitgeber time over a 48-hour period; rhythmic expressions of circadian genes and genes encoding estrogen receptor and progesterone receptor were analyzed by using the Cosinor model. The HFD, compared to the AIN93G diet, altered diurnal oscillations of circadian genes in pubertal mammary glands. These included changes in amplitude of Per2, Cry1 (reduced), Clock, Rev-erbα, and Per1 (elevated), a delay in acrophase (the hour at which the rhythm peaks) of Bmal1 by 2.2 hours, and changes in mesor (the mean of the rhythm from peak to trough) of Bmal1, Per2, Cry1 (reduced), Rev-rebα, and Per1 (elevated). Furthermore, the HFD altered diurnal expression of estrogen receptor and progesterone receptor at both mRNA and protein levels. These findings indicate that the HFD alters circadian regulation in pubertal mammary glands, which may contribute to the disturbance of hormonal homeostasis and lead to early development and growth of mammary glands in pubertal mice.